A cross-cultural study of susceptibility to the Müller-Lyer and Ponzo illusions - Smith, T V G (Rhodes University, Faculty of Humanities, Department of Psychology, 1970)
In order to investigate certain anomalies evident in the literature, the performances of three Xhosa groups (rural dwellers, urban dwellers, and undergraduates) of varying degrees of acculturation and a White undergraduate group, each group consisting of 30 subjects, were measured on tests of mode of field approach and susceptibility to the Müller- Lyer and Ponzo illusions. In addition, the effect of the introduction of a mental set, which facilitated the perception of perspective in the Ponzo figure, on susceptibility to the illusion was ascertained. Mode of field approach was measured by a portable version of the Rod-and-Frame Test. Susceptibility to the Müller-Lyer illusion was measured by a conventional movable- slide, subject-adjustable device, while a piece of apparatus which also worked on the movable slide principle and was subject-adjustable was developed to measure susceptibility to the Ponzo illusion. The set to facilitate the perception of perspective in the Ponzo figure was introduced by having subjects match the length of Ponzo contrast lines embodied in a photograph and a line-drawing of a bridge, both of these pictures having strong perspective cues. The subjects were required to perform the tasks in prescribed order. Standardised English or Xhosa instructions were ensured by the use of "programmed" worksheets for each task. Prior to each experimental task, the more unacculturated subjects performed comprehension checks to ensure that they understood the concepts of equal length and verticality. The results of the study suggested that: (i) When groups of differing acculturation levels are tested, there may be a pronounced negative association of field dependence with susceptibility to the Müller-Lyer and Ponzo illusions. In general, the more unacculturated the subject, the more field dependent and the less susceptible to illusions he was. However, there was no evidence which either strongly supported or refuted the relationship between these attributes at the intra-group level. (ii) There is no intra- group association between susceptibility to the Müller-Lyer and to the Ponzo illusions. This would indicate that they are not necessarily generated by similar inference habits or by similar contour properties. (iii) The introduction of a "perspective set" increases susceptibility to the Ponzo illusion only among acculturated subjects, who have well-developed pictorial depth perception skills and who habitually infer depth in inverted - V configurations. (iv) There is a significant association between acculturation and field independence. The unacculturated subjects, presumably because they lack the skills of visual analysis which are engendered by Western culture, were more field dependent than the acculturated subjects. (v) Provided that their degrees of acculturation are more-or-less equivalent, as were those of the two undergraduate groups, there are no differences in mode of field approach or susceptibility to the Müller-Lyer and Ponzo illusion among Xhosa and White subjects. Summary, p. 112.
Keywords: Personality and culture; Xhosa (African people) -- Psychology; Visual perception; Optical illusions; Cross-cultural studies